Literasi Informasi, Lingkungan Keluarga dan Minat Berwirausaha : Bagaimana Pengaruhnya Terhadap Perilaku Berwirausaha Siswa SMK? - Harahap, Desi Sukmayanti; Sumarno, Sumarno; Ayub, Daeng (Jurnal Paedagogy, 2023)
This study aims to analyze the causal influence of information literacy, family environment, and interest in entrepreneurship on the entrepreneurial behavior of SMK students. This research used descriptive and verification methods with a quantitative approach. The sample was students at SMK Negeri 1 Barumun, with 204 students as respondents. The research instrument used a questionnaire and an observation sheet. The data were then analyzed using multiple regression tests and path analysis. The study’s findings revealed a direct relationship between information literacy and the family environment and entrepreneurship interest. Furthermore, there was a direct relationship between information literacy and a family environment conducive to entrepreneurship and entrepreneurial behavior. Through an interest in entrepreneurship, information literacy has an indirect effect on entrepreneurial behavior. Through an interest in entrepreneurship, the family environment indirectly affected entrepreneurial behavior.